Infertile Jordanian Women’s Self-Perception About Societal Violence: An Interpretative Phenomenological Study - Bawadi H; Al-Hamdan ZM; Clark CJ; Hall-Clifford R; Hamadneh JM; Al-Sharu EE (Dove Medical Press, 2024)
Hala Bawadi,1 Zaid M Al-Hamdan,2 Cari Jo Clark,3 Rachel Hall-Clifford,4 Jehan Mahmoud Hamadneh,5 Emad Elddeen Al-Sharu6 1Maternal and Child Health Nursing Department, the University of Jordan, Amman, Jordan; 2Faculty of Nursing, Jordan University of Science and Technology, Irbid, Jordan; 3Rollins School of Public Health, Emory University, Atlanta, GA, USA; 4Center for the Study of Human Health and Department of Sociology, Emory University, Atlanta, GA, USA; 5IVF Center/ King Abdullah University Hospital, Jordan University of Science and Technology, Ar-Ramtha, Jordan; 6OB-GYN Senior Specialist Reproductive Medicine(IVF), Royal Medical Services, Amman, JordanCorrespondence: Zaid M Al-Hamdan, Email zaid_hamdan@hotmail.com; zmhamdan@just.edu.joBackground: Infertility affects one in six couples globally and is compounded by stigma and violence, particularly for women, in Jordan's culture. While existing research has illuminated societal pressures faced by infertile women, there is, yet no comprehensive understanding of the violence they encounter in their daily lives.Objective: This Interpretative Phenomenological study seeks to unravel the experiences of infertile women regarding societal violence in Jordan. By focusing on different types of community violence - physical, psychological, and emotional - The study aims to provide nuanced insights into the challenges these women confront. It also endeavors to identify contributing factors, including societal attitudes, cultural beliefs, and individual encounters, while informing policy and practice to mitigate this issue.Methods: Employing a qualitative approach, this study conducted semi-structured interviews with purposively sampled infertile women. Thematic analysis was utilized to uncover recurring patterns and themes, facilitating a comprehensive exploration of their experiences.Results: Five main themes were identified: How the surrounding people view me as an infertile woman; I am suffocated by their questions; they interfere in the smallest details; I got burned and turned to ashes, and I have no right to complain; The problem of childbearing and the treatment plan is a matter for me and my husband only; and who supports me and what do I want from those around me?Implications: This study's implications are significant for policy and practice. By foregrounding the prevalent violence faced by infertile women, it underscores the urgency of interventions. Raising awareness, providing education, and extending support can counteract societal stigma and violence. Creating a more compassionate societal fabric can ensure a safer, more inclusive environment for these women.Keywords: infertile women, community violence, societal stigma, qualitative study, Jordan, cultural norms, psychological abuse, physical violence, emotional trauma